Impact of primary care‐initiated interventions promoting physical activity on body mass index: systematic review and meta‐analysis. (23rd January 2018) - Goryakin, Y.; Suhlrie, L.; Cecchini, M.
Summary: Introduction: Physical inactivity is a risk factor for obesity, overweight and for a number of chronic diseases. Although primary care may be an ideal setting to encourage people to do more exercise, there are still significant gaps in the literature on the effectiveness of primary care‐initiated policies to promote physical activity. Methods: In this paper, we systematically review and meta‐analyse the evidence on the impact of primary care‐initiated interventions to promote exercise on the body mass index and on physical activity energy expenditure levels among people at an increased risk of having potentially disabling non‐communicable diseases (but healthy enough to exercise). Results: We find that such interventions reduce body mass index by about 0.21 kg m −2 (95% confidence interval: −0.41 to −0.01) and increase physical activity‐related energy expenditure (based mostly on self‐recall) by about 1.77 metabolic equivalent of task‐hours a week (95% confidence interval: 0.58 to 2.95). Discussion: This study suggests that primary care‐initiated interventions promoting physical activity can be an effective strategy to reduce weight and increase exercise levels in this population group, although the question remains about whether such interventions can be cost‐effective.